Konstruksi Maskulinitas melalui Fokalisasi dan Order dalam Novel Claire of the Sea Light Karya Edwidge Danticat - Cahyaning, Muthie Bunga; Priyatna, Aquarini; Adji, Muhamad (Jurnal Bahasa dan Sastra, 2026)
This article examines the construction of masculinity through two male characters, Nozias Faustin and Max Ardin Jr., in the novel Claire of the Sea Light (2013) by Edwidge Danticat, a Haitian diaspora writer. Previous studies discuss ecological concerns, postcolonial perspectives, and female characters’ resistance to patriarchy. However, the portrayal of male characters in relation to dominant norms of masculinity remains underexplored. Studies on masculinity in Haitian literature have explored colonialism, race, sexuality, and patriarchal norms, indicating a gap in the discussion of non-normative masculinity. This study aims to address this gap by analyzing how non-normative masculinity is constructed through narrative structures. The study employs close reading within Gérard Genette’s narratological framework, particularly focalization and order, as well as an intersectional masculinity framework based on class and sexuality. The study reveals two main findings. First, non-normative masculinity is negotiated differently according to class position: Nozias, a lower-class man, reconfigures fatherhood through relinquishing his child as a response to provider norms, while Max Junior, an upper-class homosexual man, adopts and performs heteronormative masculinity through sexual violence and financial support to gain patriarchal legitimacy. Second, focalization and order strategies create differences in moral accountability: the fragmented narrative with comprehensive flashbacks opens emotional and reflective space for Nozias, whereas the semi-linear narrative with limited flashbacks restricts the depiction of guilt for Max Junior. These results demonstrate that masculinity in the novel is not only socially negotiated but also structurally produced through narrative form, offering insights into gender, class, and sexuality in post-disaster Haitian contexts.